Statistical consequences of using bone mineral density to pair cadaver femurs in comparative ex vivo hip fracture studies. Issue 11 (November 2014) - Basso, T.; Klaksvik, J.; Foss, O. A.
Abstract : Objective: In ex vivo hip fracture studies femoral pairs are split to create two comparable test groups. When more than two groups are required, or if paired femurs cannot be obtained, group allocation according to bone mineral density (BMD) is sometimes performed. In this statistical experiment we explore how this affects experimental results and sample size considerations. Methods: In a hip fracture experiment, nine pairs of human cadaver femurs were tested in a paired study design. The femurs were then re-matched according to BMD, creating two new test groups. Intra-pair variance and paired correlations in fixation stability were calculated. A hypothetical power analysis was then performed to explore the required sample size for the two types of group allocation. Results: The standard deviation (sd ) of the mean paired difference in fixation stability increased from 2 mm in donor pairs to 5 mm in BMD-matched pairs. Intra-pair correlation was 0.953 (Pearson's r) in donor pairs and non-significant at -0.134 (Pearson's r) in BMD-matched pairs. Required sample size to achieve a statistical power of 0.8 increased from ten pairs using donor pairs to 54 pairs using BMD-matched pairs. Conclusion: BMD cannot be used to create comparable test groups unless sample size is increased substantially and paired statistics are no longer valid. Cite this article: Bone Joint Res 2014;3:317–20.